RETRACTED: Surgical Treatments for Canine Anterior Cruciate Ligament Rupture: Assessing Functional Recovery Through Multibody Comparative Analysis - Putame, Giovanni; Terzini, Mara; Bignardi, Cristina; Beale, Brian; Hulse, Don; Zanetti, Elisabetta; Audenino, Alberto (Frontiers in Bioengineering and Biotechnology, 2019)
Anterior cruciate ligament (ACL) deficiency can result in serious degenerative stifle injuries. Although tibial plateau leveling osteotomy (TPLO) is a common method for the surgical treatment of ACL deficiency, alternative osteotomies, such as a leveling osteotomy based on the center of rotation of angulation (CBLO) are described in the literature. However, whether a CBLO could represent a viable alternative to a TPLO remains to be established. The aim of this study is to compare TPLO and CBLO effectiveness in treating ACL rupture. First, a computational multibody model of a physiological stifle was created using three-dimensional surfaces of a medium-sized canine femur, tibia, fibula and patella. Articular contacts were modeled by means of a formulation describing the contact force as function of the interpenetration between surfaces. Moreover, ligaments were represented by vector forces connecting origin and insertion points. The lengths of the ligaments at rest were optimized simulating the drawer test. The ACL-deficient model was obtained by deactivating the ACL related forces in the optimized physiological one. Then, TPLO and CBLO treatments were virtually performed on the pathological stifle. Finally, the drawer test and a weight-bearing squat movement were performed to compare the treatments effectiveness in terms of tibial anteroposterior translation, patellar ligament force, intra-articular compressive force and quadriceps force. Results from drawer test simulations showed that ACL-deficiency causes an increase of the anterior tibial translation by up to 5.2 mm, while no remarkable differences between CBLO and TPLO were recorded. Overall, squat simulations have demonstrated that both treatments lead to an increase of all considered forces compared to the physiological model. Specifically, CBLO and TPLO produce an increase in compressive forces of 54% and 37%, respectively, at 90° flexion. However, TPLO produces higher compressive forces (up to 16%) with respect to CBLO for wider flexion angles ranging from 135° to 117°. Conversely, TPLO generates lower forces in patellar ligament and quadriceps muscle, compared to CBLO. In light of the higher intra-articular compressive force over the physiological walking range of flexion, which was observed to result from TPLO in the current study, the use of this technique should be carefully considered.